ANALISIS YURIDIS KEPUTUSAN FIKTIF POSITIF PASCA UNDANG-UNDANG NO. 6 TAHUN 2023 PERSPEKTIF SIYASAH SYAR’IYYAH - Muh. NurTaslim Saleh; Hasan, Hamzah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2025)
This research aims to find out how the juridical analysis of positive fictitious decisions after Law no. 6 of 2023 Syar'iyyah siyasah perspective. In answering this problem, the author uses a normative juridical approach and a normative theological approach (syar'i). The method for collecting secondary data in the form of primary and secondary materials is done by reading literature, scientific works, documents or books related to the research. The research results show that 1) The legal position of fictitious decisions is positive after the promulgation of the law. No. 6 of 2023, which is regulated in this Law, namely in article 175 number 7 paragraph (4), however the phrase not stipulate but grant in this article creates unclear meaning and has the potential to give rise to new problems 2) Procedures for resolving positive fictitious decisions after the issuance of the Law. No. 6 of 2023 article 175 number 7 paragraph (5) will be further regulated in a Presidential Regulation, but to date this Presidential Regulation has not been issued as a result of which the procedure for resolving positive fictitious decisions has become ambiguous and unclear. 3) The siyasah syar'iyyah view of positive fictitious decisions after the issuance of the law. No. 6 of 2023 does not explain the view of Islamic law regarding the details of positive fictitious decisions because this is purely procedural from Indonesian positive law which is administrative in nature.